Intercropping impacts the host location behaviour and population growth of aphids. Issue 1 (1st November 2019) - Mansion‐Vaquié, Agathe; Ferrer, Aurélie; Ramon‐Portugal, Felipe; Wezel, Alexander; Magro, Alexandra
Abstract: Increasing intrafield plant diversity has been shown to regulate pest populations in various agroecosystems. Among the suggested mechanisms for this bottom‐up pest control, the disruptive crop hypothesis states that herbivores' abilities to locate and colonize their host plants are reduced by the presence of non‐host plants. Under laboratory conditions, we evaluated how intercropping wheat and legumes modifies the behaviour of apterous cereal aphids, Sitobion avenae (Fabricius) (Hemiptera: Aphididae), in terms of host plant location and population growth. We compared two intercropping systems – soft winter wheat, Triticum aestivum L. (Poaceae), associated with winter pea, Pisum sativum L., or with white clover, Trifolium repens L. (both Fabaceae) – and sole stands of soft winter wheat. Aphids needed more time to locate their wheat host plant and then spent less time on wheat when it was intercropped with clover. At the population level, and accounting for host plant biomass, only intercropping wheat with clover significantly reduced aphid densities on wheat, as this was particularly disruptive to S. avenae behaviour and population growth . Our laboratory study points out that the species used as non‐host plants and their density are important parameters that should be taken into account in field studies on intercropping systems. Abstract : Intercropping cereal and legumes has been shown to regulate pest populations in various agroecosystems. Abilities of apterous cereal aphids, Sitobion avenae (Hemiptera: Aphididae), to locate and colonize their wheat host plants are reduced in wheat–clover intercrops, but not in wheat–pea intercrops. At the population level, and accounting for host plant biomass, only intercropping clover with wheat significantly reduced aphid densities.